Evaluation of Acupuncture An Intercultural and Interdisciplinary Approach - Wallner, Friedrich G.; Wallner, Friedrich G. (Peter Lang, 2018)
This book is the latest publication of the international research group (S0(BTheory, Methodology, and Structure of Traditional Chinese Medicine (TCM),(S1 (Bwhich has been working since 2008. It outlines a methodology that is adequate for research on Classical Chinese Medicine, followed by a detailed and careful analysis of Evidence-Based Acupuncture and Mechanistic Studies of Acupuncture. The authors also analyze and discuss classical texts, hermeneutical treatments, historical studies, clinical trials, women's diseases, lifestyle-related diseases, placebo effects, and Baomai and Baoluo. Leading experts from America, Austria, Brazil, China, Germany, and South Korea demonstrate that Chinese medicine is a scientific system that is independent from Western medicine.s